The Effectiveness of the Teaching Games for Understanding (TGfU) Model in Improving Students' Futsal Game Performance - Budiman Budiman; Suhada; Elzas Nurajab; Diky Hadyansah; Dadang Hermawan (STKIP Pasundan Press, 2026)
This study aimed to examine the effectiveness of the Teaching Games for Understanding (TGfU) model in improving students' futsal game performance at SMK Negeri 9 Garut, Indonesia. A quantitative approach employing a quasi-experimental method with a One Group Pretest–Posttest design was adopted. The participants consisted of 30 tenth-grade students selected through purposive sampling. Futsal game performance data were collected before and after the intervention using the Game Performance Assessment Instrument (GPAI). Data were analysed using descriptive statistics, the Shapiro–Wilk normality test, a paired-samples t-test, N-Gain analysis, and effect size. The findings revealed that the implementation of the TGfU model significantly improved students' futsal game performance. The mean score increased from 62.47 in the pretest to 81.63 in the posttest, while the paired-samples t-test indicated a statistically significant difference (p < 0.05). The N-Gain score of 0.58 indicated a moderate level of improvement, whereas the effect size demonstrated a large practical impact. These findings suggest that the TGfU model is an effective instructional approach for futsal education, as it enhances game performance, decision-making, tactical understanding, skill execution, and teamwork in authentic game situations.